Cost-effective strategies for regional road network management - Pařil, Vilém (Central European Public Administration Review, 2025)
Purpose: Our article addresses road-cost management at the regional level—an area less studied than local roads or highways. The study aims to identify critical, long-term urban factors that lead to higher regional road-management costs and to propose a financially sustainable strategy for road-network reconstruction using various reclaimed asphalt pavement (RAP) materials. Methodology: Using stepwise and enter regression analyses with data on road quality and maintenance costs in Czechia, the study considers factors such as elevation, slope, and changes in population and population density. Findings: The results highlight that slope and road class—both of which are linked to the disconnectedness of the road network—increase road-maintenance costs. Thus, network renewals implemented in compact sets of roads can significantly reduce costs. By contrast, population and population density have only a minimal impact on long-term costs. Practical Implications: We define scenarios to reduce costs through RAP materials and determine potential savings, using regional roads in Czechia as an example. The scenarios indicate potential savings of nearly €27 million per region when RAP is employed. In practice, using RAP materials can enable infrastructure managers to renew more than one-third of roads each year compared with conventional mixes, or to increase the frequency of restoring lower-quality road sections from every three years to every 2.25 years. Value: The article offers new insights into the factors that determine regional road-level costs. It demonstrates that using RAP materials in regional road management can positively affect the frequency of road revitalisation.
Keywords: critical cost factors; ključni stroškovni dejavniki; modernisation; modernizacija; načrtovanje; planning; promet; RAP; regional roads; regionalne ceste; road management; transportation; upravljanje cest